Antibacterial Films Based on MOF Composites that Release Iodine Passively or Upon Triggering by Near‐Infrared Light. (2nd February 2022) - Han, Xu; Boix, Gerard; Balcerzak, Mateusz; Moriones, Oscar Hernando; Cano‐Sarabia, Mary; Cortés, Pilar; Bastús, Neus; Puntes, Victor; Llagostera, Montserrat; Imaz, Inhar; Maspoch, Daniel
Abstract: Multidrug‐resistant bacteria have become a global health problem for which new prophylactic strategies are now needed, including surface‐coatings for hospital spaces and medical equipment. This work reports the preparation and functional validation of a metal‐organic framework (MOF) based composite for the triggered controlled release of iodine, an antimicrobial element that does not generate resistance. It comprises beads of the iodophilic MOF UiO‐66 containing encapsulated gold nanorods (AuNRs) coated with a silica shell. Irradiation of the AuNRs with near‐infrared light (NIR) provokes a photothermal effect and the resultant heat actively liberates the iodine. After validating the performance of this composite, it is integrated into a polymer for the development of antibacterial films. This work assesses the adsorption of iodine into these composite films, as well as its passive long‐term release and active light‐triggered. Finally, this work validates the antibacterial activity of the composite films in vitro against gram‐positive and gram‐negative bacteria. The findings will surely inform the development of new prophylactic treatments. Abstract : A metal‐organic framework (MOF) based composite for the uptake and near infrared (NIR) light triggered release of iodine is synthesized. This composite is integrated into a polymer for the development of prophylactic films showing passive long‐term and active light triggered release of iodine, and anti‐bacterial activity against gram‐positive and negative bacteria.